Biología Floral y Reproductiva de Plukenetia Volúbilis L. ( Euphorbiaceae)- (Sacha Inchi) - Cachique Huansi, Danter (2007)
This paper has the title "Study of the floral and reproductive biology in growing sacha inchi (Plukenetia volubilis L.); in order to assess floral morphology, development cycles, time of maturation of anthers and stigmatic. Also to study the mechanisms of pollination, floral visitors and finally determine the reproductive system more efficient; The present work was carried out in the experimental field of the Division of Genetic Resources and Biotechnology of the EE "The Future" which is located at Km 14.5 South "Fernando Belaunde Ferry" Juan Guerra District, Province and Region of San Martin Road; with a Tº 33.2º annual maximum, annual average rainfall of 1206 mm and a relative humidity of 7.7%. The statistical model used was non-parametric. The results showed that anthesis is diurnal, opening between the 5:00 a.m. to 5:30 a.m. remaining so for 35 to 48 hours. The duration of flowering inflorescences might be considered very long to take 46.65 days on average. The development of the staminate flower button and reaches 26,81días. The development of pistillate flower button and reaches 19.5 days. If fruit development register 104.5 days. On the other Plukenetia volubilis L. presents the phenomenon called dichogamy; anther dehiscence is longitudinal and coincides with the time of opening of the flowers: the stigmatic occurs with greater intensity to 96 hours after the emergence of stigma and finally cross-pollination (outcrossing) is the most efficient breeding system.